2017
DOI: 10.1186/s12864-017-3853-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic discovery of novel eukaryotic transcriptional regulators using sequence homology independent prediction

Abstract: BackgroundThe molecular function of a gene is most commonly inferred by sequence similarity. Therefore, genes that lack sufficient sequence similarity to characterized genes (such as certain classes of transcriptional regulators) are difficult to classify using most function prediction algorithms and have remained uncharacterized.ResultsTo identify novel transcriptional regulators systematically, we used a feature-based pipeline to screen protein families of unknown function. This method predicted 43 transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 122 publications
(126 reference statements)
0
20
0
Order By: Relevance
“…An entry vector containing the YFP gene was donated by Dr. Zhiyong Wang (Carnegie Institution for Science, USA) and another one, G18395, containing FLOE1's coding sequence was obtained from ABRC. The two genes were then transferred from the entry vector into the binary vector pB7HFC3_0 (Bossi et al, 2017) using Gateway cloning (Life Technologies), to create the vectors p35S:YFP-FLAG and p35S:FLOE1-FLAG. Transgenes for tobacco experiments: Arabidopsis genes: The coding sequences of FLOE1's isoforms, FLOE1.1 and FLOE1.2, were amplified by Phusion (Thermo Fisher Scientific) PCR from the entry vector G18395 using priFLOE1.1-FWD/REV and priFLOE1.2-FWD/REV (Table S3) and then BP recombined into pDONR221 (Thermo Fisher Scientific) to generate pDONR221-FLOE1.1 and pDONR221-FLOE1.2.…”
Section: Plant Plasmid Constructionmentioning
confidence: 99%
“…An entry vector containing the YFP gene was donated by Dr. Zhiyong Wang (Carnegie Institution for Science, USA) and another one, G18395, containing FLOE1's coding sequence was obtained from ABRC. The two genes were then transferred from the entry vector into the binary vector pB7HFC3_0 (Bossi et al, 2017) using Gateway cloning (Life Technologies), to create the vectors p35S:YFP-FLAG and p35S:FLOE1-FLAG. Transgenes for tobacco experiments: Arabidopsis genes: The coding sequences of FLOE1's isoforms, FLOE1.1 and FLOE1.2, were amplified by Phusion (Thermo Fisher Scientific) PCR from the entry vector G18395 using priFLOE1.1-FWD/REV and priFLOE1.2-FWD/REV (Table S3) and then BP recombined into pDONR221 (Thermo Fisher Scientific) to generate pDONR221-FLOE1.1 and pDONR221-FLOE1.2.…”
Section: Plant Plasmid Constructionmentioning
confidence: 99%
“…Sequence alignment of the C-terminal part of AtTX14 Full and related proteins, a transcriptional regulator CHIQ1 and ten CHIQLs, revealed that the C-terminal half of AtTX14 Full contains a truncated DUF641 domain (Bossi et al 2017) (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
“…We next assessed the effect of these motif sequence changes on the activity of the LPCAT1 promoter using a quantitative in planta transactivation assay ( Bossi et al, 2017 ). In this assay, we co-transformed tobacco leaves with an effector construct (35S::bZIP23 or 35S::YFP) with a reporter construct, containing either the LPCAT1 Col-0 native promoter (with GTGTC GA A motif), the LPCAT1 Col-0 mutated promoter (with GTGTC AC A motif), or the promoter of the zinc transporter ZIP4 promoter (as positive control) fused to a β-glucuronidase ( GUS )-encoding reporter gene ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…35S promoter. The 35S::C-YFP construct was provided by Dr. Seung Y. Rhee ( Bossi et al, 2017 ). Each construct was transformed into Agrobacterium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation